Layout strategy of protease production from industrial fishery wastes in Kuantan, Pahang - Shariman, Mustafa; Nurul Ain, Abdullah (Penerbit Universiti Malaysia Pahang, 2022)
Layout strategy is considered as key decision that controls long-term effectiveness of production operational activities. Fish wastes in the fisheries sector can have negative impact on the environment if not handled properly. This issue plays a huge role in the commitment for choosing the right layout suitable for production of protease from those wastes. The whole analysis of this research was conducted in Kuantan, Pahang that has concentrated many fisheries processing industries which generated quite huge tons of waste material. The purpose of this study was to define a layout strategy that was sufficient for production of protease from fishery waste. Data was obtained from interview sessions with manager of Kilang Keropok Pak Lah followed by documents review and observations of production activities for layout analysis. The study had determined the protease product process flow and therefore developed layout suited to the protease production processed from identified fishery wastes at the site. Feasibility analysis performed had determined the proposed protease production would benefit consumers, increases manufacturing capacity as well as open up new market and business opportunity for company. The study concluded that protease production from fisheries waste increases career opportunities, generate new income and bringing positive impact to the local community. From the research findings gathered, authors strongly recommended further study in this sector looking for other types of commercial products for new economic viability.